2012
DOI: 10.1007/s00709-012-0470-y
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial VDAC and hexokinase together modulate plant programmed cell death

Abstract: The voltage-dependent anion channel (VDAC) and mitochondrially located hexokinase have been implicated both in pathways leading to cell death on the one hand, and immortalization in tumor formation on the other. While both proteins have also been implicated in death processes in plants, their interaction has not been explored. We have examined cell death following heterologous expression of a rice VDAC in the tobacco cell line BY2 and in leaves of tobacco plants and show that it is ameliorated by co-expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 59 publications
2
34
0
1
Order By: Relevance
“…18 Much of the data underlying this conclusion came from the overexpression of one or other of the proteins. Here we studied the effect of reducing HxKII levels in the presence of endogenous VDAC levels.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…18 Much of the data underlying this conclusion came from the overexpression of one or other of the proteins. Here we studied the effect of reducing HxKII levels in the presence of endogenous VDAC levels.…”
Section: Resultsmentioning
confidence: 99%
“…16–18 Previous studies from our 18 as well as other 2,10 laboratories have shown that elevation in the expression of both VDAC and HxK is associated with increased growth rate as seen in cancerous cells exhibiting the Warburg Effect, 9 whereas increased expression of any one of the proteins tilts the balance of cell survival and death. 10,18 Increased expression of HxK alone makes cells resistant to cell death. 19,20 This protective effect of overexpression of HxK is limited in the absence of VDAC as shown in VDAC-silenced human dopaminergic SH-SY5Y neuroblastoma cells.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…This process induces the permeabilization of the mitochondrial OM (e.g., as a mitochondrial transition pore), which is indeed the point of no return in the intrinsic apoptotic pathway. As a proteinaceous docking platform of the outer mitochondrial membrane, VDACs interact directly with a plethora of pro-and anti-apoptotic factors, which are either members of the Bcl-2 protein family such as Bcl-xL (Malia and Wagner, 2007;Arbel et al, 2012), Bid/tBid (Rostovtseva et al, 2004), Bax/Bak (Shimizu et al, 2001) and hexokinases (Godbole et al, 2013) or Bnip3 (Chaanine et al, 2013). The precise molecular functions and stoichiometries of these VDAC/apoptotic factor complexes are poorly understood, although tentative structural predictions for several VDAC/effector complexes have been suggested (Veresov and Davidovskii, 2014).…”
Section: Non-transport Functions Of Vdacsmentioning
confidence: 99%
“…Recently, Cheng et al (2011) identified that OsHXK1, 7, and 8 in O. sativa are located in the cytoplasm and nucleus, since they lack the plastidic transit peptide and the membrane anchor domain; thus, these enzymes are classified as type-C HXKs [10]. The variety and multiple subcellular localizations of HXKs indicate that these proteins may have functions in various physiological processes of plants, such as anther dehiscence, pollen germination [11], stomatal closure [12], germination [13], programmed cell death [14], and responses to abiotic or biotic stresses [15]. It has been identified that HXKs have important roles in sugar metabolism and sugar signaling [7,16].…”
Section: Introductionmentioning
confidence: 99%